Daya Saing Karet Indonesia di Pasar ASEAN Sebelum dan Sesudah Penerapan Masyarakat Ekonomi ASEAN - Robby Alexander Sirait; Adhi Prasetyo Satrio Wibowo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
This research aims to analyze Indonesian rubber export competitiveness in the ASEAN market prior to and post-Asean Economic Community (AEC) implementation. The primary data sources in this analysis are collected from International Trade Centre and USD is used as the unit measurement analysis. The types of data in this research are taken from the period of 2012-2015 and 2016-2019. The selection of this data is expected to capture the changes that occurred prior to and post-AEC implementation. The methods in this research Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD ). The result of this research found that new pressurized tires made in Malaysia, Philipines, Thailand, and Vietnam have consistent competitiveness prior to and post-AEC.